1989
DOI: 10.1111/j.1600-0447.1989.tb10306.x
|View full text |Cite
|
Sign up to set email alerts
|

Delirium among elderly persons admitted to a psychiatric hospital: clinical course during the acute stage and one‐year follow‐up

Abstract: Seventy elderly patients meeting the DSM-III criteria for delirium were examined during the acute stage and followed up to one year. The mean age of the patients was 75 years (range 60-88), their delirium lasted on average 20 days (range 3-81) and the psychiatric hospitalization on average 30 days (range 8-365). The most common etiologies for delirium were stroke, infections and metabolic disorders. For 57 cases (81%) a predisposing structural brain disease was found. During the index admission, the cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 28 publications
4
74
0
2
Order By: Relevance
“…Almost all existing studies used IQCODE, 32,3,18 BDRS 6 , mini-mental, 6,13,14,16,18 chart review, and unspecified interviews 4,14,16 to measure cognitive performance. As we know, these methods may not discriminate between grades of cognitive impairment.…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all existing studies used IQCODE, 32,3,18 BDRS 6 , mini-mental, 6,13,14,16,18 chart review, and unspecified interviews 4,14,16 to measure cognitive performance. As we know, these methods may not discriminate between grades of cognitive impairment.…”
Section: Study Limitationsmentioning
confidence: 99%
“…6,14,17,18 Others have demonstrated that the occurrence of delirium may increase the incidence of dementia, even in patients without evidence of previous cognitive impairment. 4,13,16 A recent review of literature, including nine studies selected by means of methodological criteria, associated delirium with either a greater cognitive decline or higher incidence of dementia. 31 We believe that the difference observed in the present study results simply from the differences between the samples studied.…”
Section: Functional and Cognitive Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine were done on surgical patients, 12,19-26 11 on medical patients, 13,27-36 2 on a mixed population of medical and surgical patients, 37,38 and 5 on psychiatric patients. [39][40][41][42][43] Two of these latter studies looked at patients receiving electroconvulsive therapy. 42,43 A total of 1,365 cases of delirium were studied with 5,513 control subjects ( Table 1).…”
Section: Articles Selected and Datamentioning
confidence: 99%
“…42,43 A total of 1,365 cases of delirium were studied with 5,513 control subjects ( Table 1). The subjects in Marcantonio et al 12,23 and Koponen et al [39][40][41] were counted only once because the same population of cases was analyzed looking at different risk factors. The number of delirium cases per study varied from 8 to 301 with a mean of 59.…”
Section: Articles Selected and Datamentioning
confidence: 99%